Level of Computational Thinking and Technological Literacy Skills to Improve pre-Service Teacher Learning Innovation - Eka Budhi Santosa; Fatma Sukmawati (Universitas Pendidikan Mandalika (UNDIKMA), 2024)
This study aims to assess the extent to which teachers' technology literacy skills contribute to their ability to implement innovative teaching methods through computational thinking. This study used a quasi-experimental method with a 2x2 factorial design. This research used 84 samples of prospective teacher students from the Educational Technology Study Program. The instrument used questionnaires to assess the level of instructional innovation demonstrated by aspiring teachers, utilizing three indicators: the utilization of interactive learning media, the incorporation of information technology, and the diversity of learning resources. The statistical method employed to examine the hypothesis is a two-way analysis of variance (two-way ANOVA). The results of this study showed significant correlation between the level of students' Instructional Learning Innovation skills and Computational Thinking; the statistical analysis reveals a p-value greater than 0.05. Additionally, the research findings indicate that the level of Technological Literacy Skills has an impact on Instructional Innovation Learning skills. This research made significant contributions, such as the introduction of the Computational Thinking Level, which enables teachers to enhance their capacity to create effective learning strategies that align with the most recent advancements in technology. Technological Literacy Skills assist educators in incorporating digital tools and resources into the educational process, fostering a cutting-edge and dynamic classroom setting.